Menimbang Eksistensi Pendidikan Islam Non-formal: Mampukah Madrasah Diniyah Melengkapi Pendidikan Formal dalam Menjawab Tantangan Global? - Adnan Syah Sitorus; Chairul Bariyah; Syifa Syafriani Simatupang (Bustanul Ulum Journal of Islamic Education, 2026)
Madrasah Diniyah Takmiliyah (MDT) is a non-formal Islamic educational institution that plays a significant role in complementing Islamic religious education in Indonesia. This article aims to explore the existence and potential of MDT as a means of strengthening religious knowledge and understanding, particularly among the younger generation, which is not fully addressed by formal education. This study employs a qualitative approach through library research, analyzing various literatures, policy documents, and previous studies. The findings indicate that MDT holds great potential in reinforcing Islamic education through its accessible and community-based nature, flexible teaching methods and strategies, contextual learning materials, strong community involvement, structured levels of education, and its role in preserving Islamic culture. Nevertheless, several challenges remain, including limited teacher competence, curriculum continuity, and the need for adaptation to social changes. In conclusion, MDT not only serves as a complement to formal Islamic education but also has the potential to become a driving force of relevant, contextual, and character-based religious education, provided it is supported by professional management and adaptability to contemporary dynamics.